Cumplimiento de las normas ambientales de los establecimientos con IED en la industria automotriz y de autopartes en México - Gonzales Acolt, Roberto; Macías Acosta, Rubén; Herrera-Díaz de León, Luis Lenin (Pontificia Universidad Católica del Perú, 2025)
The objective of this study was to analyze the degree of compliance with environmental regulations in Mexico by establishments in the transportation equipment manufacturing subsector (automotive and auto parts) that have Foreign Direct Investment (FDI) participation in their share capital. To test this relationship, a logit model was used, where the dependent variable took the value 1 if the productive unit of this subsector complied with at least one environmental regulation, and 0 otherwise; the central explanatory variable was whether the economic unit of the automotive and auto parts industry with FDI, and other independent control variables were added. The results show that establishments in this industry with FDI are more likely to comply with environmental regulations. Likewise, establishments within the subsector that are classified as large enterprises, organized into corporate groups, and located in the central-western region exhibit a higher likelihood of complying with environmental regulations. Furthermore, the establishments in this industry that carry out other practices to improve and care for the environment are more likely to implement environmental standards. The main result of the study supports the halo hypothesis, as a positive and significant effect was found regarding compliance with environmental regulations by of the transport equipment manufacturing establishments with FDI.

El objetivo de esta investigación consistió en analizar el grado de cumplimiento de las normas de carácter ambiental en México por los establecimientos del subsector de fabricación de equipo de transporte (automotriz y autopartes) que en su capital social tienen participación de Inversión Extranjera Directa (IED). Para probar esta relación, se empleó un modelo logit, donde la variable dependiente fue 1 si la unidad productiva de este subsector cumplió con alguna norma en materia de medioambiente, y 0 en caso contrario; la variable explicativa central fueron las unidades económicas de la industria automotriz y de autopartes con IED; además, se agregaron otras variables independientes de control. Los hallazgos muestran que las unidades económicas de esta industria con IED tienen mayores probabilidades de cumplir con alguna norma ambiental. Asimismo, los establecimientos del subsector que son grandes empresas, conformados en grupos empresariales y ubicados en la región Centro Occidente, presentan una probabilidad mayor de aplicar la normatividad ambiental. También, las unidades económicas de esta industria que llevan a cabo otras prácticas de mejora y cuidado del medioambiente tienen mayores probabilidades de ejecutar normas ambientales. El resultado principal del estudio se aproxima a la hipótesis halo, pues se comprueba un efecto positivo y significativo en el cumplimiento de las normas de carácter ambiental por parte de los establecimientos de fabricación de equipo de transporte con participación de IED.
Compliance with the Environmental Regulations of FDI Establishments in the Automotive and Auto Parts Industry in Mexico
Keywords: Environmental regulations; Foreign Direct Investment (FDI); Manufacturing of transportation equipment; Halo hypothesis; Mexico; Normas de carácter ambiental; Inversión Extranjera Directa (IED); Fabricación de equipo de transporte; Hipótesis halo; México; https://purl.org/pe-repo/ocde/ford#2.07.01